If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 7 + -1(6x + 2) = 0 Reorder the terms: 14x + 7 + -1(2 + 6x) = 0 14x + 7 + (2 * -1 + 6x * -1) = 0 14x + 7 + (-2 + -6x) = 0 Reorder the terms: 7 + -2 + 14x + -6x = 0 Combine like terms: 7 + -2 = 5 5 + 14x + -6x = 0 Combine like terms: 14x + -6x = 8x 5 + 8x = 0 Solving 5 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 8x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = 0 + -5 8x = 0 + -5 Combine like terms: 0 + -5 = -5 8x = -5 Divide each side by '8'. x = -0.625 Simplifying x = -0.625
| (x-9)(4x+7)=0 | | 6x-4.7=1.1 | | 25=-2(m-8)+5m | | y+14=-3 | | 3x+7.7-3.4=0-3.4 | | 2=2(m-8)-5m | | 10x-22=78 | | x+4-3x=-12 | | 5x+3.4=2x+4.3 | | 3x+3.3=-3.4 | | x^2+29x+23= | | 10-9x=79-30x | | 7n-9=-39+n | | 25-2y=6y+5 | | 5x-9=4x-11 | | 8+3p=8p+4 | | 7p-25=2p | | 7+18z-6=7z+27-2z | | 3x+8=-46 | | 5t-1.5=14.1+1.1t | | -5g=35 | | 6(s+.3)=18 | | -z-1(z-6)=8 | | 6(x-3)-1=3x+3(-5+x) | | -6x-8x=-56 | | n-29-33=-49 | | 0.7c+0.34d-0.13c+0.3d= | | 8(4x-2)=48 | | 9x+7=7x-19 | | 19m+8+7m+31= | | 18-5x=7x+4(x-1)-5(8-3x) | | 8x+7x=90 |